ChemInform Abstract: Highly Enantioselective Synthesis of Chiral Tetrahydroquinolines and Tetrahydroisoquinolines by Ruthenium‐Catalyzed Asymmetric Hydrogenation in Ionic Liquid. Issue 20 (20th May 2014) - Ding, Zi‐Yuan; Wang, Tianli; He, Yan‐Mei; Chen, Fei; Zhou, Hai‐Feng; Fan, Qing‐Hua; Guo, Qingxiang; Chan, Albert S. C.
Abstract This method uses chiral phosphine‐free Ru(diamine) complexes as catalysts which can be recycled 5‐6 times without a significant loss in activity.